EFFECTS OF ARBUSCULAR MYCORRHIZA FUNGI, ORGANIC FERTILIZER AND DIFFERENT MOISTURE REGIMES ON SOIL PROPERTIES AND YIELD OF AMARANTHUS CRUENTUS - Adewole, Moses Bamidele; Adewole, Moses B.; Adekanmbi, Adebisi E. (Journal of Agricultural Sciences (Belgrade), 2019)
Abstract: A pot experiment was conducted to assess the influence of two arbuscular mycorrhiza (AM) fungi and organic fertilizer (OF) on the growth and yield of Amaranthus cruentus under varying soil moisture regimes with a view to providing information on the crop adaptation to drought conditions and to also sustain soil nutrient balance for increased crop yields. The experiment consisted of 36 treatments [(Glomus clarum, Glomus deserticola and no AM), organic fertilizer made from market wastes at different rates (0, 5 and 10 t ha-1) and varied water regimes (25, 50, 75 and 100% field capacity (FC)]. Each of the treatment was replicated thrice. The treatment combination, 10 t ha-1 OF and G. clarum produced the highest fresh vegetative yield of 48.82 t ha-1 which was not significantly (p > 0.05) different from only 45.78 t ha-1 fresh yield obtained with 5 t ha-1 OF and G. clarum when water levels were compared. The repeat experiment with only water addition gave lower and comparable yields of A. cruentus. We concluded that the addition of G. clarum in combination with 5 t ha-1 of organic fertilizer to soil optimally improved the growth and yield of A. cruentus in water stress conditions.